Emergence of the third-generation cephalosporin-resistant hypervirulent Klebsiella pneumoniae due to the acquisition of a self-transferable blaDHA-1-carrying plasmid by an ST23 strain - Yingzhou Xie; Lijun Tian; Gang Li; Hongping Qu; Jingyong Sun; Wei Liang; Xiaobin Li; Wang Xiaoli; Zixin Deng; Jialin Liu; Hong‐Yu Ou (2018)
KEYWORDS: blaDHA-1conjugation transfercomparative genomic analysishypervirulent Klebsiella pneumoniaemultidrug resistant plasmid